Individualisation of Training and Prevention in Sprinting: The FULGUR Project - Giroux, Caroline (Réflexions Sport, 2024)
At the Olympic Games, maximal speed running is the most frequently performed action by athletes, with the 100m being considered the flagship event. However, achieving such sprinting speeds requires not only highly developed physical abilities but also a robust musculoskeletal system to avoid excessive injury risk. Indeed, lower limb muscle injuries, which are heavily solicited during sprinting, are the leading cause of training or competition interruptions on the international stage. France stands out historically for its excellence in speed sports and is recognized for its research in sports science applied to understanding sprint performance. Within this context, the FULGUR project pursues three main objectives: to describe sprint mechanics at the center of mass and joint segment levels, in order to quantify sprint-specific training loads at these scales, under real-world training or even competition conditions (Work Package 1); to determine the musculoskeletal profile of each elite athlete with the aim of offering “tailor-made” training programs to optimize sprint propulsion efficiency (Work Package 2); to estimate the injury risk level and suggest individualized prevention strategies based on a multifactorial approach that includes environmental factors (nutrition, sleep) and athlete behavior (Work Package 3). These objectives will be supported by cross-cutting work packages aimed at improving the analysis of musculoskeletal imaging and sports movement using ultrasound techniques and machine learning.
Keywords: sprint; strain injuries; tailored training; athlete availability